2017
DOI: 10.1016/j.envres.2017.04.029
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopment for the first three years following prenatal mobile phone use, radio frequency radiation and lead exposure

Abstract: We found no association between prenatal exposure to RFR and child neurodevelopment during the first three years of life; however, a potential combined effect of prenatal exposure to lead and mobile phone use was suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 25 publications
1
21
0
3
Order By: Relevance
“…Population-based studies have revealed that women exposed to RF-EMF during pregnancy have adverse effects on the neurodevelopment of offspring, and increase their odds of emotional and behavioral difficulties (Sudan et al, 2016;Choi et al, 2017). Studies focus on adolescents students exposed to mobile phones or base stations have revealed that RF-EMF exposure is associated with the impairment of spatial memory, attention deficiency, and delayed motor skills (Foerster et al, 2018;Meo et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Population-based studies have revealed that women exposed to RF-EMF during pregnancy have adverse effects on the neurodevelopment of offspring, and increase their odds of emotional and behavioral difficulties (Sudan et al, 2016;Choi et al, 2017). Studies focus on adolescents students exposed to mobile phones or base stations have revealed that RF-EMF exposure is associated with the impairment of spatial memory, attention deficiency, and delayed motor skills (Foerster et al, 2018;Meo et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This, and a limited number of other mammal-based studies [5] suggest that developmental exposures to RFR can result in adverse effects. However, there also exists evidence to the contrary, with several epidemiological studies suggesting a lack of effects unequivocally attributable to RFR exposure [12]. Most of the published RFR studies are based on previous generations of telecommunication RFRs.…”
Section: Introductionmentioning
confidence: 99%
“…17 Interestingly, there is no study to date that can confirm any of these hypotheses. 7 Wired-in hands-free kits (HFKs) can considerably reduce RFR exposure to the head, 18 which is inconsistent with the results of Sudan et al, 13 that found that the use of a handsfree device during pregnancy was associated with the increased risk. The highest ORs for migraines were found in the groups that often used hands-free devices, followed by those who "rarely used hands-free devices" and "never used hands-free devices."…”
Section: Discussionmentioning
confidence: 97%